Pelatihan Pemanfaatan Geogebra dalam Pembelajaran Matematika di SMA YPPK Asisi Sentani, Jayapura - Ida M. Hutabarat; Irfan Wahyudi; Radian J. Situmeang; Yacob Ruru (LPPM Uncen, 2025)
One of the computer programs that can be used as a medium for learning mathematics is the GeoGebra program. With various facilities, GeoGebra can be used as a medium for learning mathematics to demonstrate or visualize mathematical concepts and as a tool to construct mathematical concepts. This community service (PKM) aims to determine the effect of GeoGebra-assisted learning on students' understanding of mathematical concepts in algebra material. The stages used in this service consist of 3 stages, namely: 1) Preparation stage, 2) implementation stage, 3) final stage. The method used to support the success of this program is in the form of training, demonstrations and exercises/practice or tutorials. This PKM activity went well and has made a positive contribution to students in using the GeoGebra application in learning mathematics and gaining additional knowledge and new skills.